The Role of RNA in DNA Breaks, Repair and Chromosomal Rearrangements - Matvey Mikhailovich Murashko; Ekaterina Mikhailovna Stasevich; Anton Markovich Schwartz; Dmitriy Vladimirovich Kuprash; Aksinya Nicolaevna Uvarova; Denis Eriksonovich Demin (Biomolecules, 2021)
Incorrect reparation of DNA double-strand breaks (DSB) leading to chromosomal rearrangements is one of oncogenesis’s primary causes. Recently published data elucidate the key role of various types of RNA in DSB formation, recognition and repair. With growing interest in RNA biology, increasing RNAs are classified as crucial at the different stages of the main pathways of DSB repair in eukaryotic cells: nonhomologous end joining (NHEJ) and homology-directed repair (HDR). Gene mutations or variation in expression levels of such RNAs can lead to local DNA repair defects, increasing the chromosome aberration frequency. Moreover, it was demonstrated that some RNAs could stimulate long-range chromosomal rearrangements. In this review, we discuss recent evidence demonstrating the role of various RNAs in DSB formation and repair. We also consider how RNA may mediate certain chromosomal rearrangements in a sequence-specific manner.